Relationship Between Instructional Leadership of School Administrators under the Office of the Private Education Commission, Bangkapi District and 21st Century Skills of Learners: - doni, mahama; Rumakhom, Vassiga; Adulvajarameta, Somchart (Mahachula Academic Journal, 2024)
This research is a quantitative and qualitative research. The objectives of this research were to (1) study instructional leadership of school administrators under the Office of the Private Education Commission, Bangkapi district and (2) study 21st century skills of learners of schools under the Office of the Private Education Commission, Bangkapi district (3) study relationship between instructional leadership of school administrators under the Office of the Private Education Commission, Bangkapi district and 21st century skills of learners. The sample consisted of 155 teachers of schools under the Office of the Private Education Commission, Bangkapi district and interview 5 school administrators. The tool used in this research was the questionnaire and interview form. Statistical analysis methods used to analyze the data were frequency distribution, percentage, mean, standard deviation, Pearson’s correlation coefficient and content analysis. The results have shown as followed, (1) instructional leadership of school administrators under the Office of the Private Education Commission, Bangkapi district as whole was at a high level. (2) 21st century skills of learners of schools under the Office of the Private Education Commission, Bangkapi district as whole was at a high level. (3) There was a positive, moderate level relationship between instructional leadership of school administrators under the Office of the Private Education Commission, Bangkapi district and 21st century skills of learners.